Bariery fiansowania rozwoju polskiego sektora MSP na tle wybranych krajów Unii Europejskiej - Duda, Joanna (Barriers of Financing of Polish SME Sector Development Against the Background of Chosen EU Countries, 2006)
Small and medium enterprises play an important role in the whole economy. They fill niches in the market, slum flexibility in the adaptation to changing environment and contribute to the competitiveness increase. They create new workplaces and have a significant share in the creation of GNP. However, on the contrary lo the firms functioning in Germany and Finland, SME sector in Poland has trouble in gelling financial resources from outer sources. Polish entrepreneurs encounter many barriers limiting their development, not only of capital, but also of legal and legislation kind. That is why the financing sources of SME sector in chosen regions of EU is compared in this paper while an attempt to identify the piers limiting the development of small and medium enterprises in Poland is made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 160-171